The Free, Childlike Play and the Strengthening of the Parent-Child Relationship: A Report from the Linkage of University Teaching and Practice - Peatzold, Ulrich (Wydawnictwo Naukowe UAM, 2015)
The basic works on the importance of play for children's development emphasize the holistic and comprehensive importance for all areas of development. As part of the various approaches of pedagogy these effects were harnessed in recent decades and functionalized for different societal and social goals. Though the original meaning of children's play is increasingly faded in professional circles and is seen in its possibilities rather mainly in performanceoriented goals. Most likely the client-centered play therapy still pursues the original sense of the play, focusing on the actual needs of the child in its totality and individuality. As part of a project at the the BTU Cottbus students of Social Work / Social Pedagogy meet families for weekly play visits, to exemplary encourage the parents to play with their children themselves. The low-threshold project aims to have a preventive effect and to strengthen the parent-child relationship.
Keywords: original meaning of children’s play; client-centered play therapy